Sleuthing the Bible : clues that unlock the mysteries of the text - Kaltner, John, 1954-; McKenzie, Steven L., 1953- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2019)
"For scholars the Bible is a book of mysteries to be solved: Who wrote the text? When and why was it written? How can I make sense of these customs? Does this text relate to real history? This book explains the sort of detective work to biblical scholarship that entails finding and interpreting clues that help to answer such questions"--
The clue of the intrusive narrator -- The clue of the physical description -- The clue of the etiology -- The clue of the weird social custom -- The clue of the inconsistency -- The clue of the doublet -- The clue of the echo -- The clue of the repeated pattern -- The clue of the broken pattern -- The clue of the telegraphed information -- The clue of the name -- The clue of the anachronism -- The clue of the hidden meaning -- The clue of the messy manuscript -- The clue of the perspectival bias.
Includes bibliographical references and index.
Keywords: Bible -- Hermeneutics; Bible -- Criticism, interpretation, etc